METHODOLOGICAL ISSUE IN PRAGMATIC RESEARCH: IS DISCOURSE COMPLETION TEST A RELIABLE DATA COLLECTION INSTRUMENT? - Lusia Marliana Nurani (Fakultas Seni Rupa dan Desain ITB, 2009)
In pragmatic research One of the data collection instrument whichreleability is being questioned about its reliability is the Discourse Completion Test (DCT). This issue appears due to several weaknesses of DCT. Firstly, the authenticity of the situations is limited. Then, the hypothetical nature of the situations in DCT simplifies the complexity of interactions in real conversation. Moreover, what people claim they would say in the hypothetical situation is not necessarily what they actually say in real situations. In addition, DCT is not able to bring out the extended negotiation which commonly occurs in authentic discourse due to the absence of interactions between interlocutors. Despite its disadvantages, DCT allows researchers to collect a large amount of data in a relatively short time. Furthermore, DCT creates model responses which are likely to occur in spontaneous speech. DCT also provides stereotypical responses for a socially appropriate response. DCT is also an appropriate instrument for interlanguage pragmatic research because it can be applied directly to participants coming from different cultural backgrounds. In dealing with the drawbacks of DCT, further research is needed to evaluate the reliability and validity of DCT. Strengthening the design of DCT may allow this instrument to collect data more carefully and reliably in order to improve the quality of the study. Applying multi instruments of data collection in a study will also enhance the quality of the data as well as the study. Key words: DCT, pragmatic, speech act, reliability